Izšla še zadnja knjiga posodobljenega velikega komentarja posebnega dela KZ-1 - Koritnik, Boštjan (Pravnik, 2024)
In Slovenian history, the Criminal Code (KZ-1) had not been scientifically commented on in depth within the ambit of a large-scale research project. To describe the situation as unsatisfactory with regard to legal culture would be an understatement. In 2015, such research was finally undertaken in Slovenia, culminating in March 2019 with the publication of the first scientific commentary on the special part of the Criminal Code. Authored by 47 contributors and assisted by 33 professionals, this commentary was released in three volumes. The project was led by editors-in-chief being Katja Filipčič and Damjan Korošec, both from the University of Ljubljana, Faculty of Law. More than 3,000 pages were written on 291 Criminal Code articles. Since the first edition, four amendments have been adopted, with interventions in sexual and commercial criminal law being among the most theoretically and practically demanding. By March 2023, with contributions from additional experts, all three volumes of the revised commentary were published, extending to 4,238 pages.
Keywords: amendment; criminal code; criminal law; Faculty of Law; kazenski zakoniki; kazensko pravo; novele; Official Gazette of the Republic of Slovenia; Pravna fakulteta; raziskave; research; University of Ljubljana; Univerza v Ljubljani; Uradni list Republike Slovenije